2008
DOI: 10.1007/978-1-4020-8831-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Hepatic Fatty Acid Metabolism

Abstract: The liver is a major site of fatty acid synthesis and degradation. Transcriptional regulation is one of several mechanisms controlling hepatic metabolism of fatty acids. Two transcription factors, namely SREBP1-c and PPARalpha, appear to be the main players controlling synthesis and degradation of fatty acids respectively. This chapter briefly presents fatty acid metabolism. The first part focuses on SREBP1-c contribution to the control of gene expression relevant to fatty acid synthesis and the main mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 227 publications
(267 reference statements)
1
64
1
1
Order By: Relevance
“…In fact, our group previously demonstrated that the hypotriglyceridemic effect of GSPE in vivo acts through an FXR-and SHP-dependent mechanism (21,22). GSPE-enhanced FXR activity up-regulates the expression of SHP, which in turns represses SREBP1c, the transcription factor that controls the expression of hepatic genes involved in FA and TG synthesis (75). Now, we have reported a decrease of lipogenesis in HFD ϩ GSPE rats through the expression of an extended number of proteins.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, our group previously demonstrated that the hypotriglyceridemic effect of GSPE in vivo acts through an FXR-and SHP-dependent mechanism (21,22). GSPE-enhanced FXR activity up-regulates the expression of SHP, which in turns represses SREBP1c, the transcription factor that controls the expression of hepatic genes involved in FA and TG synthesis (75). Now, we have reported a decrease of lipogenesis in HFD ϩ GSPE rats through the expression of an extended number of proteins.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, gene ontology-based (GO-based) enrichment analysis of differentially expressed genes in Pml-WT and -KO liver extracts identified a significant overrepresentation of genes related to lipid metabolism (P = 1.29 × 10 -5 ; Figure 2, A and B). FAO is a tightly regulated metabolic process, which is under strict transcriptional control (29). Surprisingly, promoter analysis of genes related to lipid metabolism modulated in Pml-KO (Figure 2, A and B) revealed a significant enrichment of peroxisome proliferatoractivated receptor-response element-containing (PPRE-containing) genes (0.27 sites per Kb, P = 0.006; Supplemental Table 2), in line with the notion that PPAR complexes play a critical role in the regulation of FAO (30,31).…”
Section: Pml Opposes a Metabolic Syndrome In Vivo By Favoring Fatty Amentioning
confidence: 99%
“…Furthermore, J. montana polyphenols may decrease mRNA expression of acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS)], the rate-limiting enzymes of fatty acid synthesis in the liver, and mRNA expression of [sterol regulatory element-binding protein (SREBP)-1c [73] , which controls the expression of these enzymes. [74] These findings indicate that the anti-obesity actions of J. montana ethanolic extract are may due to increased expression of energy expenditure-related genes in liver and decreased fatty acid synthesis and fat intake in the liver. On the other hand, Insulin resistance can be generated by decreased adiponectin secretion and decreased TNF-α secretion.…”
Section: Discussionmentioning
confidence: 91%